CefixView: understanding trends in respiratory infections - Choudhari, Sachin; Pawar, Dattatray; Bhure, Anjali; Ade, Apurva (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Respiratory tract infections (RTIs) are one of the most common infections in humans of all age groups and an important cause of mortality and morbidity worldwide. It can be classified as either acute or chronic. The bacterial species most commonly implicated in RTIs are Streptococcus pneumoniae, β-hemolytic Streptococci, Hemophilus influenzae, and Moraxella catarrhalis. Cefixime, a third-generation cephalosporin, is a bactericidal β-lactam antibiotic used to treat various bacterial infections. It is broad-spectrum and effective against gram-positive as well as gram-negative bacteria. The primary objective is to understand the preferences, considerations, and clinical perspectives that influence the choice of cefixime among healthcare professionals, particularly in the management of RTIs. Methods: It was a descriptive questionnaire-based cross-sectional study. The study was conducted among the physicians who attended the APICON-2024 and gave consent to participate in the study. A total 247 physicians registered their responses. Results: Cefixime is preferred in indications like UTI, pharyngitis, Otitis media, typhoid fever, LRTIs, shigellosis, and dental infections. All the doctors (100%) use cefixime for the treatment of RTIs with varied frequency. The primary factor which influences the choice of cefixime for the management of RTIs is the broad-spectrum activity (46.75%) followed by a better safety profile (27.87%) and cost-effectiveness (15.08%). Overall, 92.73% of doctors view cefixime as a safe and reliable choice for the management of RTIs. Conclusions: Cefixime has excellent tolerability and efficacy and is one of the most widely used drug in the treatment of respiratory infections.